Fish assemblage responses to flow seasonality and predictability in a tropical flood pulse system. Issue 11 (9th November 2018) - Ngor, Peng Bun; Oberdorff, Thierry; Phen, Chheng; Baehr, Christophe; Grenouillet, Gaël; Lek, Sovan
Abstract: Hydropower dams are looming in the Mekong Basin, affecting river flows that structure aquatic communities. Here, we quantitatively assessed flow seasonality and predictability in three sites located in three rivers displaying a gradient in flow alterations caused by upstream dams and investigated how fish assemblages responded seasonally and inter‐annually to this gradient. By analyzing 7‐yr daily fish and water monitoring data, we found that dams disturbed the natural flow seasonality and predictability. While the river displaying the lower seasonality–predictability was characterized by a distinct seasonal variation in assemblage composition with high species turnover, rivers with stronger flow seasonality–predictability exhibited broadly similar seasonal patterns in fish assemblage composition with low species turnover and regular annual peaks of fish migration. These results challenge the expectation of higher species turnover in systems displaying higher flow seasonality and predictability and may be partly due to the strong adaptation of fish assemblages to these specific systems. By enhancing our understanding of biological systems in the highly seasonal–predictable and aseasonal–unpredictable environments of the lower Mekong system, these findings suggest that hydropower‐related pulsed flows that can mimic as far as possible natural pulsed flows are critical to reduce downstream effects on aquatic organisms.